A Qualitative Study of “What Matters” to Older Adults in the Emergency Department - Gettel, Cameron; Venkatesh, Arjun; Dowd, Hollie; Hwang, Ula; Ferrigno, Rockman; Reid, Eleanor; Tinetti, Mary (The western journal of emergency medicine, 2022)
Introduction: The “4Ms” model – What Matters, Medication, Mentation, and Mobility – is increasingly gaining attention in age-friendly health systems, yet a feasible approach to identifying what matters to older adults in the emergency department (ED) is lacking. Adapting the “What Matters” questions to the ED setting, we sought to describe the concerns and desired outcomes of both older adult patients seeking ED care and their treating clinicians. Methods: We conducted 46 dyadic semi-structured interviews of cognitively intact older adults and their treating clinicians. We used the “What Matters” conversation guide to explore patients’ 1) concerns and 2) desired outcomes. We then asked analogous questions to each patient’s treating clinician regarding the patient’s priorities. Interviews were professionally transcribed and coded using an inductive approach of thematic analysis to identify emergent themes. Results: Interviews with older adults lasted a mean of three minutes, with a range of 1–8 minutes. Regarding patients’ concerns, five themes emerged from older adults: 1) concern through a family member or outpatient clinician recommendation; 2) no concern, with a high degree of trust in the healthcare system; 3) concerns regarding symptom cause identification; 4) concerns regarding symptom resolution; and 5) concerns regarding preservation of their current status. Regarding desired outcomes, five priority themes emerged among older adults: 1) obtaining a diagnosis; 2) returning to their home environment; 3) reducing or resolving symptoms; 4) maintaining self-care and independence; and 5) gaining reassurance. Responding to what they believed mattered most to older adult patients, ED clinicians believed that older adults were concerned primarily about symptom cause identification and resolution and primarily desired a return to the home environment and symptom reduction. Conclusion: This work identifies concerns and desired outcomes of both older adult patients seeking ED care and their treating clinicians as well as the feasibility of incorporating the “What Matters” questions within ED clinical practice.